How can IT enable economic growth in developing countries - Avgerou, Chrisanthi (1998)
Reviews theories on the economic significance of IT and telecommunications, and discusses the nature of the economic effects that should be expected from the diffusion of these technologies and increased emphasis on information activities. Suggests that developing countries should make efforts to develop organisational practices which are locally appropriate and not simply seek to transfer 'best practice' for doing business.